USE OF ARTIFICIAL INTELLIGENCE TO IDENTIFY AND CORRECT MISCONCEPTIONS ABOUT RADIATION - Oleksandr Tymoshchuk (Інформаційні технології і засоби навчання)
The expansion of nuclear technologies in various industries, combined with the constant threat of radiation-related incidents, highlights the urgent need for effective radiation education. This study is devoted to an empirical investigation of the effectiveness of artificial intelligence tools (neurological models of artificial intelligence) in detecting and correcting